IMPROVING GRAMMAR MASTERY BY USING DYNAMIC ASSESSMENT TO THE 7th YEAR STUDENTS OF SMP N 1 KETANGGUNGAN IN 2010/2011 ACADEMIC YEAR - Ratnaningtyas, Aprilia (2011)
The general objective of this research is to improve the students' grammar mastery. While the specific objectives of this research are to describe the implementation of Dynamic Assessment on teaching grammar in the 7th year students of SMP N 1 Ketanggungan and to describe whether Dynamic Assessment can improve the students' grammar mastery. In achieving the objectives of this research, the writer uses Classroom Action Research (CAR). Each cycle of this action research consists of four steps: planning, acting, observing, and reflecting. The research was held in SMP N 1 Ketanggungan consisting of 33 students. In analyzing the data, the writer uses both qualitative and quantitative analysis taken from observation, test, and interview. There are two cycles in this action research in which each cycle is conducted in two meetings. The result of the study shows that the mean score of pre test is 33.9, Cycle I is 43.7, and in Cycle II 66.9. it indicates that the students have an improvement in grammar mastery. Through Dynamic Assessment, the students became more active and creative in grammar material. They could write and speak in right form of tenses. Thus, it can be said that teaching grammar through Dynamic Assessment is Sucessfull to improve the students' grammar mastery in SMP N 1 Ketanggungan.